18.6k views
2 votes
3+2(x-6)+5-3(x+4)=6x

2 Answers

0 votes

Simplifying

3 + 2(x + -6) + 5 + -3(x + 4) = 6x


Reorder the terms:

3 + 2(-6 + x) + 5 + -3(x + 4) = 6x

3 + (-6 * 2 + x * 2) + 5 + -3(x + 4) = 6x

3 + (-12 + 2x) + 5 + -3(x + 4) = 6x


Reorder the terms:

3 + -12 + 2x + 5 + -3(4 + x) = 6x

3 + -12 + 2x + 5 + (4 * -3 + x * -3) = 6x

3 + -12 + 2x + 5 + (-12 + -3x) = 6x


Reorder the terms:

3 + -12 + 5 + -12 + 2x + -3x = 6x


Combine like terms: 3 + -12 = -9

-9 + 5 + -12 + 2x + -3x = 6x


Combine like terms: -9 + 5 = -4

-4 + -12 + 2x + -3x = 6x


Combine like terms: -4 + -12 = -16

-16 + 2x + -3x = 6x


Combine like terms: 2x + -3x = -1x

-16 + -1x = 6x


Solving

-16 + -1x = 6x


Solving for variable 'x'.


Move all terms containing x to the left, all other terms to the right.


Add '-6x' to each side of the equation.

-16 + -1x + -6x = 6x + -6x


Combine like terms: -1x + -6x = -7x

-16 + -7x = 6x + -6x


Combine like terms: 6x + -6x = 0

-16 + -7x = 0


Add '16' to each side of the equation.

-16 + 16 + -7x = 0 + 16


Combine like terms: -16 + 16 = 0

0 + -7x = 0 + 16

-7x = 0 + 16


Combine like terms: 0 + 16 = 16

-7x = 16


Divide each side by '-7'.

x = -2.285714286


Simplifying

x = -2.285714286

Hope this helps!

User Scott Weldon
by
5.0k points
7 votes
5(x-6)+2(x+4)=6x
5x-30+2x+8=6x
User Altercation
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.